The current state of sustainability reporting: opportunities and challenges for consultancy companies : strategizing for successful sustainability reporting and turning emerging trends into business opportunities - Shoturma, Vladyslava (2022)
Sustainability reporting is undoubtedly among the main concerns for companies, namely data selection and collection, automatization of reporting processes, and adaptability to ever changing legislation. The work project examines what is the current European panorama and how can consultancy companies leverage its resources to take advantage of emerging opportunities. Such analysis was conducted through extensive research and interviews. It concludes that forthcoming legislation and investor pressure are driving demand for sustainability reporting services, and that a company’s challenge may be another’s business opportunity. Furthermore, additional research on the Portuguese market can, and should, be conducted to provide better recommendations.